DETERMINATION OF BUFFER STOCK BETWEEN PREVENTIVE MAINTENANCE ACTIVITIES FOR REPAIRABLE PRODUCTION SYSTEMS - Ho, Jyh-Wen; Yang, Jian-Yi; Huang, Yeu-Shiang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This study considers the economic manufacturing quantity model of a repairable system with two production processes in which the manufacturer can evaluate the setup problems between the two during the planning period due to the effects of preventive maintenance. We estimate the expected maintenance cost of component failures with consideration of preventive maintenance intervals for the upstream production process and demand conditions for the downstream assembly system to determine the optimal buffer stock with the minimum expected total cost of the production system. An illustrative example verifies that the inventory holding cost greatly affects the optimal buffer size, followed by the downstream production rate and the reset time. Furthermore, the optimal quantity of the buffer stock and preventive maintenance intervals determined by the proposed approach can assist managers in devising adequate strategies when planning preventive maintenance during a steady production process.